Estimation of soil loss sensitivity in the Jinari river basin using the Universal Soil Loss Equation - Kalita, Nilotpal; Borgohain, Akangsha; Sahariah, Dhrubajyoti; Sarma, Siddhinath (National Geographical Journal of India, 2022)
Soil erosion hazard is an environmental problem in diverse geographical areas and oftentimes has repercussions that are felt in downstream areas. This study assesses various aspects of soil erosion in the Jinari River basin in Assam, India using the Universal Soil Loss Equation (USLE) in a GIS environment. The average rainfall erosivity index is found as 165.2 MJ mm/ha/yr and soil erodability factor K varies between 0.56 - 0.43. The LS factor was computed using Digital Elevation Model (DEM) data, while the C factor was computed from Normalized Difference Vegetative Index (NDVI) values derived from Landsat TM data. In the Jinari River basin no supporting practice was observed, thus the value of ’P’ has been taken as 1. The average annual soil loss estimated in the watershed using USLE was 1.76 ton/ha/yr and 0.95 ton/ ha/yr for 2007 and 2011 respectively.